The Relationship between Obesity and the Incidence of Osteoarthritis in the Working Area of the Lampaseh Health Center in 2025 - Nurul Fitria; Cut Putri Riska (Jurnal Impresi Indonesia, 2025)
Objective: To build public awareness of the importance of maintaining body mass index as the first step in detecting the risk of joint damage and preventing osteoarthritis (OA) cases. Methods: A descriptive observational method with a cross-sectional approach was used in this study. This research was carried out in January-March 2025 using primary and secondary data. The total sample amounted to 41 respondents. Results: The study's results based on the BMI category were obtained from the number of osteoarthritis patients who were obese, as many as 26 people (63.4%). This study shows that osteoarthritis sufferers who are obese, the highest occurs in women, namely 24 people (92.3%), most of them are in the age group of ? 60 years (12 people (46.1%), the majority are housewives, namely 23 people (88%), and most of them have osteoarthritis in the knee joint, which is 22 people (84%).  Conclusion: Most of the osteoarthritis respondents were obese.